Early‐term deliveries as an independent risk factor for long‐term respiratory morbidity of the offspring. Issue 2 (26th July 2016) - Walfisch, Asnat; Beharier, Ofer; Wainstock, Tamar; Sergienko, Ruslan; Landau, Daniella; Sheiner, Eyal
Summary: Objective: Newborns exhibit the lowest immediate respiratory morbidity rates when born following 39 completed weeks of gestation. We sought to determine whether early‐term delivery (37–38 + 6 weeks' gestation) impacts on long‐term pediatric respiratory morbidity. Study design: In this population‐based prospective cohort analysis, all term singleton deliveries occurring between 1991 and 2013 at a single tertiary medical center were included. Gestational age upon delivery was sub‐divided into: early (37–38 + 6 weeks' gestation), full (39–40 + 6 weeks' gestation), late (41–41 + 6 weeks' gestation), and post‐term (>42 weeks) deliveries. The incidence of long‐term hospitalizations (up to the age of 18 years) of the offspring due to a set of predefined respiratory morbidities was evaluated. Survival curves were used to compare cumulative morbidity incidence. A Cox hazards regression model was used to control for confounders. Results: During the study period, 229, 142 term deliveries met the inclusion criteria. Of those, 24% (n = 55, 202) occurred at early term. Hospitalizations up to the age of 18 years, as a result of complications in the respiratory system were significantly more common in the early‐term group as compared with full and late‐term delivery groups. In the Cox regression model, while controlling for multiple confounders, early‐term delivery exhibited an independent association with long‐term respiratory morbidity (adjusted HR = 1.24, CI 1.19–1.29, P  < 0.001). Conclusion: Deliveries occurring at early term are associated with higher rates of pediatric respiratory hospitalizations compared with full and late‐term deliveries.Pediatr Pulmonol. 2017;52:198–204. © 2016 Wiley Periodicals, Inc.